2019
DOI: 10.1042/bsr20191878
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8 facilitates proliferation and immune evasion of esophageal cancer cells

Abstract: Correspondence: Xiaojun Liu (ergesulju2012@163.com)Esophageal cancer is seen with increasing incidence, but the underlying mechanism of esophageal cancer is still unknown. Transient receptor potential melastatin (TRPM) is non-selective cation channels. It has been verified that TRPM channels play crucial roles in development and progression of multiple tumors. Increasing studies have shown that TRPM8, a member of TRPM channels, promotes growth of tumors. However, it is still unclear whether TRPM8 has biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…TRPC6 mRNA expression levels are increased in human EC tissues compared to normal tissues [ 40 ]. The knock-down and inhibition of TRPM8 may decrease the proliferation of EC cells [ 41 ]. In addition, a higher expression of TRPV2 protein has been shown to be correlated with a worse 5-year overall survival rate after surgery [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRPC6 mRNA expression levels are increased in human EC tissues compared to normal tissues [ 40 ]. The knock-down and inhibition of TRPM8 may decrease the proliferation of EC cells [ 41 ]. In addition, a higher expression of TRPV2 protein has been shown to be correlated with a worse 5-year overall survival rate after surgery [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that SPINK5 acted as a tumor suppressor by suppressing the Wnt/beta-catenin pathway in ESCA [ 18 ]. Lan et al proved that TRPM8 facilitated cell growth and immune evasion in ESCA cells [ 19 ]. RSRC2 was proved to be a tumor inhibitor and a prognostic target gene inESCA [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown and inhibition of TRPM8 decrease proliferation of esophageal cancer cells. Moreover, TRPM8 negatively regulates PD-L1 expression through the calcineurin-NFATc3 pathway, enabling the immune evasion of ESCC cells [72].…”
Section: Trpv2mentioning
confidence: 99%